2013
DOI: 10.1038/ncomms3316
|View full text |Cite|
|
Sign up to set email alerts
|

Glycogen shortage during fasting triggers liver–brain–adipose neurocircuitry to facilitate fat utilization

Abstract: During fasting, animals maintain their energy balance by shifting their energy source from carbohydrates to triglycerides. However, the trigger for this switch has not yet been entirely elucidated. Here we show that a selective hepatic vagotomy slows the speed of fat consumption by attenuating sympathetic nerve-mediated lipolysis in adipose tissue. Hepatic glycogen pre-loading by the adenoviral overexpression of glycogen synthase or the transcription factor TFE3 abolished this liver–brain–adipose axis activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 16 publications
1
65
0
2
Order By: Relevance
“…We therefore conclude that neither changes in de novo lipogenesis nor changes in lipid oxidation contributed to the decrease in hepatic lipid content in the HFD-fed PTG OE mouse group. A recent study revealed that glycogen shortage in the liver triggers the liver-brain-adipose tissue neural axis independently of glucose and insulin/glucagon levels, thus playing a key role in switching the fuel source from glycogen to triglycerides under prolonged fasting conditions (48). The present results support these observations because overnight-fasted PTG OE mice had higher glycogen levels than control mice.…”
Section: Discussionsupporting
confidence: 82%
“…We therefore conclude that neither changes in de novo lipogenesis nor changes in lipid oxidation contributed to the decrease in hepatic lipid content in the HFD-fed PTG OE mouse group. A recent study revealed that glycogen shortage in the liver triggers the liver-brain-adipose tissue neural axis independently of glucose and insulin/glucagon levels, thus playing a key role in switching the fuel source from glycogen to triglycerides under prolonged fasting conditions (48). The present results support these observations because overnight-fasted PTG OE mice had higher glycogen levels than control mice.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, when food is scarce, the liver becomes the storage site for triacylglycerols (TAGs), thus acting as a reservoir of energetic substrates that can be liberated [51]. When the stored TAGs are depleted, the free fatty acids (FFAs) and glycerol released are directly oxidized as an energy source by certain tissues (liver and muscle) [50]. Moreover, adenosine triphosphate can be produced through the oxidation of FFAs, and glycerol can be used as a substrate in gluconeogenesis or lipogenesis Fasting, Cognitive Performance and Exercise [50].…”
Section: Intermittent Fastingmentioning
confidence: 99%
“…IF enhances parasympathetic activity (mediated by the neurotransmitter acetylcholine) in the autonomic neurons that innervate the gut, heart, and arteries, resulting in improved gut motility and reduced heart rate and blood pressure. By depleting glycogen from liver cells, fasting also results in lipolysis [49,50]. In addition, when food is scarce, the liver becomes the storage site for triacylglycerols (TAGs), thus acting as a reservoir of energetic substrates that can be liberated [51].…”
Section: Intermittent Fastingmentioning
confidence: 99%
“…In order to meet the systemic energy demands during a fast, hormonal signals stimulate adipose tissue to release non-esterified fatty acids (NEFA) into circulation at a rate which exceeds clearance by non-hepatic tissues (Patel et al 2002, Djurhuus et al 2004. Additionally, depression of hepatic glycogen stores during fasting further stimulates adipose tissue lipolysis, indicating that in addition to external hormonal signals, internal liverderived signals regulate systemic energy metabolism and promote lipid mobilization (Izumida et al 2013). To better clear circulating fatty acids, the liver upregulates expression of the hepatic fatty acid transporter Cd36 (Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%